Confess : a novel - Hoover, Colleen (New York, NY : Atria Books, 2015)
At age twenty-one, Auburn Reed has already lost everything important to her. In her fight to rebuild her shattered life, she has her goals in sight and there is no room for mistakes. But when she walks into a Dallas art studio in search of a job, she doesn't expect to find a deep attraction to the enigmatic artist who works there, Owen Gentry. For once, Auburn takes a chance and puts her heart in control, only to discover that Owen is keeping a major secret from coming out. The magnitude of his past threatens to destroy everything important to Auburn, and the only way to get her life back on track is to cut Owen out of it. To save their relationship, all Owen needs to do is confess. But in this case, the confession could be much more destructive than the actual sin.
Keywords: Artists' studios -- Texas -- Dallas -- Fiction; Man-woman relationships -- Fiction; Artists -- Fiction; Confession -- Fiction; Secrets -- Fiction; Man-woman relationships; Dallas (Tex.) -- Fiction; Fiction; Love stories; Romance fiction; Love stories